2000
DOI: 10.1016/s0002-9440(10)64527-0
|View full text |Cite
|
Sign up to set email alerts
|

Human Decidua Contains Potent Immunostimulatory CD83+ Dendritic Cells

Abstract: The human uterus is generally considered to be an immunologically privileged site that isolates the implanted allogeneic embryo from an aggressive maternal immune response. This is in contrast to the fact that the decidua, like other mucosal surfaces, must be able to respond to different types of foreign antigens, including pathogenic organisms, seminal plasma, and fetal trophoblasts (FTBs). However, during hemochorial placentation, the direct contact between FTBs (which invade uterine mucosa, the decidua) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
144
0
4

Year Published

2001
2001
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 183 publications
(152 citation statements)
references
References 38 publications
4
144
0
4
Order By: Relevance
“…We can also hypothesize that the increase in the expression of NKp30 may be one of the pathways that results in the significant increase of mature DC seen in the late-secretory stage of the menstrual cycle [26][27][28][29]. These data also suggest a mechanism for how the epithelium may initiate the process of establishing immune tolerance in the decidua, at the time of trophoblast invasion.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…We can also hypothesize that the increase in the expression of NKp30 may be one of the pathways that results in the significant increase of mature DC seen in the late-secretory stage of the menstrual cycle [26][27][28][29]. These data also suggest a mechanism for how the epithelium may initiate the process of establishing immune tolerance in the decidua, at the time of trophoblast invasion.…”
Section: Discussionmentioning
confidence: 89%
“…Endometrial epithelium has been shown to have antigen-presenting ability, a capability that is under hormonal control [22][23][24]. Recent studies have shown that the numbers of mature and immature DC significantly increase in endometrium during the latesecretory phase and early pregnancy [25][26][27][28][29]. These observations raise the possibility that NKp30 may have a role in promoting immune tolerance while maintaining immune surveillance in the endometrium during embryo implantation.…”
Section: Discussionmentioning
confidence: 99%
“…The decidual cell population consists of several immunological cells, and a disturbance in the distribution of phenotype of these cells may lead to pregnancy complications. Macrophages and DCs are present in the human decidua, 6,19,24,25 and an alteration of the phenotype and distribution may be involved in the pathogenesis of preeclampsia. 26 The sequential stained immunohistochemical slides showed that, in general, CD14 ϩ cells also can be DC SIGN ϩ and CD163 ϩ .…”
Section: Discussionmentioning
confidence: 99%
“…In human decidua, DCs are relatively sparse compared with macrophages (w1% of total decidual cells (Kammerer et al 2000)), questioning the functional importance of these cells in the decidua (Rieger et al 2004). Macrophages and DCs share the ability to act as APCs, and both cells may therefore coordinate innate and adaptive immune responses in human pregnancy by balancing maternal immune responses against foreign antigens with protection of the semi-allogenic conceptus (Kammerer et al 2000). First-trimester human CD83 C decidual DCs possess T cell immune-stimulatory capacity in ex vivo mixed leukocyte reactions and also cluster with T cells in situ (Kammerer et al 2000).…”
Section: Dendritic Cellsmentioning
confidence: 99%
“…Macrophages and DCs share the ability to act as APCs, and both cells may therefore coordinate innate and adaptive immune responses in human pregnancy by balancing maternal immune responses against foreign antigens with protection of the semi-allogenic conceptus (Kammerer et al 2000). First-trimester human CD83 C decidual DCs possess T cell immune-stimulatory capacity in ex vivo mixed leukocyte reactions and also cluster with T cells in situ (Kammerer et al 2000). Decidual DCs appear to be more tolerogenic than their peripheral blood counterparts, with a lower capacity for antigen presentation, reduced expression of co-stimulatory molecules, reduced expression of inflammatory cytokines such as IL12 and enhanced expression of anti-inflammatory cytokines such as IL10 (Laskarin et al 2007, Arck et al 2013.…”
Section: Dendritic Cellsmentioning
confidence: 99%